THE EFFECT OF PROMOTION, PRICE PERCEPTION, AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF TYM.WASH SHOE LAUNDRY IN BABAT-LAMONGAN - Vionarisca Kurnia Putri; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine the influence of promotion, price perception, and service quality on customer satisfaction. The population in this study consists of customers of Tym.Wash shoe laundry services in Babat-Lamongan. The sampling technique used in this research is the Lemeshow technique. The type of data used in this research is quantitative data. The data collection technique used in this study is a questionnaire. The data analysis tests include Convergent Validity, Average Variance Extracted (AVE), Cronbach's Alpha, and R-Square tests.